KAJIAN IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN IPS DI SMP NEGERI 2 MANGANITU KABUPATEN KEPULAUAN SANGIHE - Serlina Surapina Br Torong; Erick Lobja; Grystin Djein Sumilat (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2020)
This research problem is related to the implementation of the 2013 curriculum in social studies subjects at SMP Negeri 2 Manganitu, Sangihe Islands Regency. This study aims to examine the implementation of the 2013 curriculum on IPS subjects at SMP Negeri 2 Manganitu, Sangihe Islands Regency. The research method used is descriptive qualitative. The research focus is the study of the 2013 curriculum implementation and the sub-focus of this research is the condition of facilities, teacher preparation, student readiness. The informants in this study were the principal, deputy principal in the curriculum field, subject teachers and students of SMP Negeri 2 Manganitu, Kepulauaun Sangihe Regency. Primary data were collected using observation techniques (direct observation), interviews, and documentation and FGD (Focus Group Discussion). The data analysis technique used in this study was the Milles and Huberman technique. Determination of informants in this study using purposive sampling and snowball sampling techniques. The results showed, the condition of the facilities in the school was still incomplete, such as inadequate opening lesson packages so that students were not allowed to bring textbooks to their homes, inadequate internet networks, Lack of teacher readiness in implementing the 2013 curriculum implementation of learning methods boring, student dwellings that are far from school. So that the process of implementing the 2013 curriculum has not been maximal to apply.